2017
DOI: 10.1007/s00429-016-1349-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute restraint stress decreases c-fos immunoreactivity in hilar mossy cells of the adult dentate gyrus

Abstract: Although a great deal of information is available about the circuitry of the mossy cells (MCs) of the dentate gyrus (DG) hilus, their activity in vivo is not clear. The immediate early gene c-fos can be used to gain insight into the activity of MCs in vivo, because c-fos protein expression reflects increased neuronal activity. In prior work, it was identified that control rats that were perfusion-fixed after removal from their home cage exhibited c-fos immunoreactivity (ir) in the DG in a spatially stereotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 64 publications
7
35
1
Order By: Relevance
“…The low number of c-Fos-immunoreactive MCs in dorsal DG is consistent with prior studies of HCNOE (Bernstein et al, 2019; see also Duffy et al, 2013;Moretto et al, 2017) Next, we compared relatively rostral and more caudal coronal sections. Tukey's post-hoc tests revealed that in rostral sections, eDREADD mice (14.72 ± 1.87 cells) had significantly more hilar c-Fos cells per section than control (2.22 ± 0.31 cells) and iDREADD mice (1.90 ± 0.32 cells; all p values <0.001; Figure 10C).…”
Section: Hilar C-fossupporting
confidence: 79%
See 4 more Smart Citations
“…The low number of c-Fos-immunoreactive MCs in dorsal DG is consistent with prior studies of HCNOE (Bernstein et al, 2019; see also Duffy et al, 2013;Moretto et al, 2017) Next, we compared relatively rostral and more caudal coronal sections. Tukey's post-hoc tests revealed that in rostral sections, eDREADD mice (14.72 ± 1.87 cells) had significantly more hilar c-Fos cells per section than control (2.22 ± 0.31 cells) and iDREADD mice (1.90 ± 0.32 cells; all p values <0.001; Figure 10C).…”
Section: Hilar C-fossupporting
confidence: 79%
“…These findings are an important confirmation that eDREADD treatment increased neuronal activity of hilar neurons during this task. The hilar neurons were probably MCs because we previously found that HCNOE preferentially activates MCs compared to other hilar neurons after HCNOE (Duffy et al, 2013;Moretto et al, 2017;Bernstein et al, 2019) and DREADDs were preferentially expressed in MCs (Figure 1).…”
Section: Hilar C-fosmentioning
confidence: 89%
See 3 more Smart Citations